Surface Interactions and Mechanical Properties Shaping Biofilm Dynamics in S. aureus and P. aeruginosa - Shaista Urooj (Journal of Global Antimicrobial Resistance)
This study comprehensively investigates biofilm formation, and exploring its various biophysical properties like adhesion, surface roughness, cell stiffness, and cell surface hydrophobicity. The study is focused on five foodborne biofilm-positive strains of Pseudomonas (P) aeruginosa and Staphylococcus (S) aureus. After isolation, antimicrobial susptibility testing and molecular identification of the isolates, biofilm of all the strains was developed, and analyzed using the crystal violet assay. Subsequently, biofilm slides were assessed through Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM) to study the biophysical attributes. AFM findings revealed water reduction during biofilm formation, demonstrating variations in the rate at which water content decreased. Specifically, P. aeruginosa exhibited faster initial force increases on glass surfaces (τ = 4 s) compared to cell-to-cell surfaces (τ = 21 s). Moreover, AFM-based cell stiffness measurements indicated a decreasing trend in P. aeruginosa during biofilm maturation (48 hrs: 0.6 MPa, 96 hrs: 1.3 MPa) with an oscillatory behavior. The S. aureus consistently exhibited a decrease in stiffness over time, with values of 0.9 MPa at 48 hrs and 1.3 MPa at 96 hrs. Additionally, an increase in cell surface hydrophobicity during biofilm stages indicated enhanced water repellency in both species. SEM further revealed distinctive connectivity tubes within P. aeruginosa and S. aureus biofilms, facilitating intercellular communication. This study brings forth new angles for developing targeted, species-specific approaches to address biofilm challenges. Understanding the multifaceted phenomena of biofilm formation and development enables the design of interventions that disrupt key processes, promising more effective biofilm control.